Metal‐Organic Frameworks for Gene Therapy and Detection. (12th January 2023) - He, Yaping; Li, Daifeng; Wu, Li; Yin, Xianzhen; Zhang, Xiaojian; Patterson, Laurence H.; Zhang, Jiwen
Abstract: Gene therapy holds great promise as a biomedicine for treating cancer, viral infection, and recessive gene disorders, while genetic detection has been used for disease diagnosis and prevention. The appropriate carrier is crucial to improve the delivery efficiency of nucleic acids. Although viral and nonviral delivery vectors have been developed, their poor nucleic acid loading efficiency, off‐target toxicity, and immunogenicity significantly hamper their use. Metal‐organic frameworks (MOFs) have attracted a lot of attention owing to their high surface areas and tunable structures. Recently, nanometric MOFs are shown to be promising nonviral vectors in gene delivery and detection although at an early stage of development. This review focuses on highlighting the current status and promising breakthroughs of MOF use in nucleic acid delivery, including siRNA, miRNA and mRNA delivery, DNA gene delivery and transfection, as well as probes for detection of gene expression. This study will help promote the clinical transformation and application of gene modulation, gene delivery, and detection that use of MOFs can offer. Abstract : Metal‐organic frameworks (MOFs) are promising nonviral vectors for gene therapy and detection owing to their precision tunability, high surface areas, and high loading capacities. This review focuses on highlighting the current status and promising breakthroughs of MOF use in nucleic acid delivery, including mRNA, siRNA, and miRNA delivery, DNA gene delivery and transfection, and probes for detection of gene expression.